2009
DOI: 10.1152/ajpgi.90568.2008
|View full text |Cite
|
Sign up to set email alerts
|

Krüppel-like factor 4 regulates adaptive expression of the zinc transporterZip4in mouse small intestine

Abstract: Liuzzi JP, Guo L, Chang S-M, Cousins RJ. Krüppel-like factor 4 regulates adaptive expression of the zinc transporter Zip4 in mouse small intestine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 38 publications
2
49
0
2
Order By: Relevance
“…It was reported that zinc status had little effect on transcription of Zip4 but rather regulated mRNA stability both in cultured Hepa cells and mouse intestine (21). In contrast, a recent study found that Krüppel-like factor 4 bound to Zip4 promoter and its knockdown impaired Zip4 induction by zinc depletion in a mouse intestinal epithelial cell line (23). At the protein level, apart from endocytosis stimulated by low micromolar zinc (24), ubiquitination and degradation of ZIP4 were observed under higher zinc levels (25).…”
Section: Zinc Uptake Across the Apical Membrane Into Enterocytesmentioning
confidence: 94%
“…It was reported that zinc status had little effect on transcription of Zip4 but rather regulated mRNA stability both in cultured Hepa cells and mouse intestine (21). In contrast, a recent study found that Krüppel-like factor 4 bound to Zip4 promoter and its knockdown impaired Zip4 induction by zinc depletion in a mouse intestinal epithelial cell line (23). At the protein level, apart from endocytosis stimulated by low micromolar zinc (24), ubiquitination and degradation of ZIP4 were observed under higher zinc levels (25).…”
Section: Zinc Uptake Across the Apical Membrane Into Enterocytesmentioning
confidence: 94%
“…Luminescence from firefly luciferase were normalized to renilla after 24 h incubation with 100 μM ZnSO 4 . These methods have been described in detail earlier (42,43). See SI Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Up-regulation of SLC39A4 transcripts during zinc deficiency might be due to mRNA stabilization rather than increased transcription of its gene (Weaver et al, 2007). However, the Krüppel-like factor 4 (KLF4) transcription factor was suggested to be responsible for regulating ZIP4 expression (Liuzzi et al, 2009). KLF4 is abundant in the intestine, induced during zinc restriction in mice, and binds to the mouse Slc39a4 promoter (Liuzzi et al, 2009).…”
Section: Zinc Uptake and Its Regulationmentioning
confidence: 99%